2020
DOI: 10.3390/su12229587
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Commuting: Results from a Social Approach and International Evidence on Carpooling

Abstract: Sustainable commuting (SC) usually refers to environmentally friendly travel modes, such as public transport (bus, tram, subway, light rail), walking, cycling, and carpooling. The double aim of the paper is to summarize relevant prior results in commuting from a social approach, and to provide new, international empirical evidence on carpooling as a specific mode of sustainable commuting. The literature shows that certain socio-demographic characteristics clearly affect the use of non-motorized alternatives, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…During the COVID-19 pandemic, people's preferences for modes of transportation did not change. Another multicountry study suggests that carpooling appears to be slightly decreasing in the COVID-19 pandemic [9]. During the COVID-19 pandemic, only the rate of private transportation and motorcycles increased.…”
Section: Traveler Perceptions and Usage Of Carpooling In Karachimentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, people's preferences for modes of transportation did not change. Another multicountry study suggests that carpooling appears to be slightly decreasing in the COVID-19 pandemic [9]. During the COVID-19 pandemic, only the rate of private transportation and motorcycles increased.…”
Section: Traveler Perceptions and Usage Of Carpooling In Karachimentioning
confidence: 99%
“…Globally, travel demand management strategies have been implemented to address transportation challenges [7,8]. Carpooling fleets are rapidly expanding, including in China, France, the United States, Europe, the Netherlands, Greece, India, and Canada [9]. Carpooling is a type of sharing economy, in which individuals pool their vehicles to utilize a service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by the size of our corpus and the two most recent meta-analyses on the topic [7,18], carpooling has long been a topic of numerous academic studies during the last decade. Our analysis of the main research topics underlines that many of the selected papers have investigated the profile of carpoolers [29][30][31][32]-or, more often, people expressing an intention to carpool [1,[33][34][35][36]]-compared to non-carpoolers, and their main motivations to practice carpooling [13,37]. Findings revealed that psychological dimensions, such as attitude towards carpooling, enjoyment of being sociable, trust in other people, environmentalist identity and the role of the family circle and peer group, are more influential than classical socio-demographic, economic and spatial variables [38][39][40][41][42].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Studies are also needed on the impacts on the other shared modes of transport, such as carpooling. In particular, carpooling could be less impacted than public transport or it could even benefit from the situation since it could be considered less risky than public transport [32,158,159] due to fewer people or because carpooling apps could require sanitary guarantees such as a health pass. On the other hand, carpooling could be considered a risky transport mode compared to solo driving.…”
Section: Modal Choice After the Pandemicmentioning
confidence: 99%